Case Report: Cystinosis in a Chinese Child With a Novel CTNS Pathogenic Variant - Guan, Yu-Jia; Guo, Yan-Nan; Peng, Wen-Tao; Liu, Li-Li (Frontiers in Pediatrics, 2022)
Objective To report a rare case of cystinosis with a novel CTNS pathogenic variant in the Chinese population. Methods Retrospective analysis of the clinical manifestations, laboratory results, and gene detection data of a child with cystinosis. Results A Chinese Zang ethnic girl could not stand or walk until 3 years old, with additional symptoms including a loss of appetite. Since then, the girl gradually exhibited “X” leg, double wrist joints, a bilateral ankle deformity, and rickets. At the age of 9 years, the girl was hospitalized. Laboratory testing showed that her blood phosphorus, blood calcium and blood potassium levels were significantly decreased. At the same time, the girl's urine glucose and urine protein were positive, although her fasting blood glucose, glycosylated hemoglobin, and 75 g glucose tolerance were not significantly abnormal. Further, blood gas analysis showed metabolic acidosis. These symptoms corresponded to Fanconi syndrome. Gene analysis showed that there was a homozygous pathogenic variant c.140 ≤ 5G > A (p.?) in the CTNS gene, which was a small variation in the intron region. To our knowledge, this is the first report of the rare variant. Conclusion Attention should be paid to the differential diagnosis of cystinosis by gene analysis in children whose clinical manifestations include exercise dysplasia, renal damage, or multiple organ damage (including bone, thyroid, etc) and who cannot be firmly diagnosed for the time being.